The relationship of depressive symptoms in cancer patients with treatment by chemotherapy. - Khudhair, Ali K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: depressed mood and anxiety are common symptoms in hospitalized cancer patients .it is often presumed that anxiety and depression affect the occurrence and experience of physical symptoms . the researcher was aimed to assess the level of depression among cancer patients and the chemotherapy side effects and to find out the significant difference between depression level regarding these side effects.Patients and methods: A descriptive analytical study was conducted on a purposive sample of 50 cancer patients from both sexes who were admitted to Radiation and Neuclur Medicine Hospital in Baghdad for the purpose of giving chemotherapy for the period from April 4th to June 20th , 2008. A structured interview using the Self Care Diary (SCD) of Nail et al (1991) and Hospital Anxiety and Depression Scale (HADS) was implemented for data collection.Results: It was found that cancer patient has a significant level of depression and the relationship between depression and presence of chemotherapy side effects in hospitalized cancer patients is not significant.Conclusions: there is no relationship between depression and chemotherapy side effects but it may be due to the disease it self.